Comprehensive chiroptical spectroscopy. Volume 1, - Berova, Nina; Polavarapu, Prasad L.; Nakanishi, Koji; Woody, Robert W. (Wiley, 2012)
"This book provides an introduction to the important methods of chiroptical spectroscopy in general, and circular dichroism (CD) in particular, which are increasingly important in all areas of chemistry, biochemistry, and structural biology. The book can be used as a text for undergraduate and graduate students and as a reference for researchers in academia and industry, with or without the companion volume in this set. Experimental methods and instrumentation are described with topics ranging from the most widely used methods (electronic and vibrational CD) to frontier areas such as nonlinear spectroscopy and photoelectron CD, as well as the theory of chiroptical methods and techniques for simulating chiroptical properties. Each chapter is written by one or more leading authorities with extensive experience in the field."--Resumé vydavatele